2011
DOI: 10.1007/s00705-011-0927-x
|View full text |Cite
|
Sign up to set email alerts
|

The small nuclear ribonucleoprotein U1A interacts with NS5 from yellow fever virus

Abstract: The flavivirus NS5 protein is one of the most important proteins of the replication complex, and cellular proteins can interact with it. This study shows for the first time that the yellow fever virus (YFV) NS5 protein is able to interact with U1A, a protein involved in splicing and polyadenylation. We confirmed this interaction by GST-pulldown assay and by co-immunoprecipitation in YFV-infected cells. A region between amino acids 368 and 448 was identified as the site of interaction of the NS5 protein with U1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…As reported previously [30], the production of a homology model for the RNA polymerase domain of the YFV NS5 protein showed that this region of interaction (ID) is exposed and potentially capable of forming interactions. We also demonstrated that ID from the dengue 4, dengue 3, and Saint Louis encephalitis viruses interact with eIF3L, suggesting that this interaction is important for other members of the genus.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…As reported previously [30], the production of a homology model for the RNA polymerase domain of the YFV NS5 protein showed that this region of interaction (ID) is exposed and potentially capable of forming interactions. We also demonstrated that ID from the dengue 4, dengue 3, and Saint Louis encephalitis viruses interact with eIF3L, suggesting that this interaction is important for other members of the genus.…”
Section: Discussionmentioning
confidence: 69%
“…We also demonstrated that ID from the dengue 4, dengue 3, and Saint Louis encephalitis viruses interact with eIF3L, suggesting that this interaction is important for other members of the genus. Accordingly, when the YFV sequence was compared to the sequences of other flaviviruses, a region of homology from residues 20 to 80 was identified [30]. Mutations in the FWELV motif of ID abolished the interaction with eIF3L, suggesting that the amino acids FWELV are critical for the ID interaction with eIF3L.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that, during viral replication, the methyltransferase domains of the flavivirus NS5 proteins recruit cellular factors kinases (CK1 and PKG), 46,47 mitochondrial trifunctional protein (MTP), 48 and PSD-95/Dlg/ ZO-1 proteins, 49,50 while the RdRp domains can interact with the nuclear import receptors importin-α and importin-β, 43,51 cyclophilin A, 52 heat shock protein 70 (Hsp70), 53 protein kinase G (PKG), 40 L subunit of human eukaryotic translation initiation factor 3 (eIF3L), 54 and small nuclear ribonucleoprotein U1A. 55 These factors can enhance formation of the replication complex, RNA stability, genome translation, and/or posttranslational modification. 56,57 Considering the remarkable difference in YFV transmission cycles between Africa and South America, 58,59 the existence of the adaptive changes might favor the interaction between NS5 and cellular factors from different host and (or) vector.…”
Section: Discussionmentioning
confidence: 99%
“…Interaction of NS5 with the host protein U1A occurs at a site that is highly conserved across various flaviviruses, and may represent potential broad-spectrum inhibition of viral replication (Bronzoni et al, 2011). Knowledge of these various cellular components that are important in virus replication may result in novel targets for inhibition of YFV and also strengthens the case to develop broad-spectrum inhibitors of flavivirus NS3 and NS5.…”
Section: Targeting the Virusmentioning
confidence: 99%